Comparison of the intensity of pain in patients with acute cholecystitis with different types of surgical accesses - Hordiienko, Polina Oleksiivna; Sochnieva, Anastasiia Lvovna (KRPOCH Publishing House, 2021)
Background: Topicality is related to the widespread prevalence of acute cholecystitis as one of the surgical pathologies. There are 3 types of surgical access for cholecystectomy: laparotomy, laparoscopic and mini-laparotomy in the right hypochondrium. At the postoperative period, patients complain of the pain that occurs at the site of the surgical wound. Intensity of pain depends on the type of surgery. The aim of the study: To analyze and compare the intensity of postoperative pain in different types of surgical accesses in patients with acute cholecystitis. Methods: The study was performed at the State Institution “V. T. Zaitsev Institute of General and Urgent Surgery of the National Academy of Medical Sciences of Ukraine” on the treatment of acute cholecystitis from 2019 to 2021. 30 case histories of patients with acute cholecystitis were analyzed. Patients were divided into 3 groups: Group I - 24 (80.00%) patients underwent laparoscopic cholecystectomy, Group II – 5 (16.67%) – with mini-access and Group III – 1 (3.33%) – laparotomy due to the pronounced adhesion process of the abdominal organs. The intensity of pain was assessed by using a Visual Analog scale. Results: According to the results of the assessment of pain intensity by Visual Analog scale: patients of Group I on the 2nd day after surgery noted pain at the level 50±8.75 mm, on the 5th day – 0 mm, patients of the II Group on the 2nd day – 70±9.32 mm, on the 5th day – 20±5.88 mm. Group III on 2nd day – 90±8.85 mm, on 5th day – 40±2.87 mm. Conclusions: The use of laparoscopic access in the surgical treatment of acute cholecystitis improves the quality of life of patient in the postoperative period and reduces pain.
Keywords: postoperative pain syndrome; laparoscopy; laparotomy; cholecystectomy; mini-laparotomy in the right hypochondrium